Total availability of journal articles to Internet users - White BD (Emerald Group Publishing, 2014)
Purpose - To determine the outcome of the different measures taken towards open accessto peer-reviewed research by measuring aggregate availability of a sample of journal articles.This sample was then used to examine the factors contributing to the availability or non-availability of types of article. Design/methodology/approach - A sample of articles was taken from the Scopus database based on a search by surname. This minimised any skew that would result from a datasetbased on subject or source. The results were analysed to determine availability by subject and differences in availability based on source. Findings - Less than 30% of articles are available in their year of publication, rising to nearly 40% in following years. Repositories are responsible for slightly less than 50% of available articles. Substantial differences exist between the practices of scholarly societies and commercial publishers. Practical implications - Aggregate availability is dependent on a range of activities and current efforts need to be maintained to ensure its continuance. Moves towards open access by commercial publishers are not a major factor. Originality/value - This study differs from similar work by looking at access from the users’ viewpoint. Rather than looking at the total amount of material to which access is provided, it looks at the proportion of high-value information which is available. Read the article at http://www.massey.ac.nz/~bwhite/totalavailability.pdf
"This article is (c) Emerald Group Publishing and permission has been granted for this version to appear here http://dx.doi.org/10.1108/LR-01-2014-0006. Emerald does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from Emerald Group Publishing Limited."
Keywords: Information democracy; Open access; Institutional repositories; Access to information; Scholarly publishing; Learned society publishing; 0807 Library and Information Studies